2011
DOI: 10.1007/s00253-011-3567-x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the nargenicin A1 pyrrole moiety from Nocardia sp. CS682

Abstract: A number of structurally diverse natural products harboring pyrrole moieties possess a wide range of biological activities. Studies on biosynthesis of pyrrole ring have shown that pyrrole moieties are derived from L-proline. Nargenicin A(1), a saturated alicyclic polyketide from Nocardia sp. CS682, is a pyrrole-2-carboxylate ester of nodusmicin. We cloned and identified a set of four genes from Nocardia sp. CS682 that show sequence similarity to the respective genes involved in the biosynthesis of the pyrrole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The strains were seeded in brain heart infusion (BHI) broth at 37°C for 5 days. Nargenicin A 1 aglycon has been shown to be derived from common precursors as acetate and propionate [23], and the pyrrole moiety is presumed to be derived from L-proline [24,25]. In the present study, the influence of precursor substrates including ethanol, glucose, and glycerol as source of acetate, propanol as source of propionate, and L-proline contributing for pyrrole moiety, was evaluated on nargenicin A 1 biosynthesis.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 98%
“…The strains were seeded in brain heart infusion (BHI) broth at 37°C for 5 days. Nargenicin A 1 aglycon has been shown to be derived from common precursors as acetate and propionate [23], and the pyrrole moiety is presumed to be derived from L-proline [24,25]. In the present study, the influence of precursor substrates including ethanol, glucose, and glycerol as source of acetate, propanol as source of propionate, and L-proline contributing for pyrrole moiety, was evaluated on nargenicin A 1 biosynthesis.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 98%
“…Studies have shown that biosynthesis of the 5-methylpyrrolyl-2-carboxyl moiety present in clorobiocin and coumermycin A 1 , the dichloropyrrolyl moiety in pyoluteorin, the pyrrolyl-2-carboxyl moiety in leupyrrins, and the first of the three pyrrole groups in undecylprodigiosin, can be all traced back to the pyrrole-2-carboxylate skeleton in all the cases, regardless of parent compounds and the microbial strain employed as a producing agent. In the case of leupyrrins, aminocoumarin antibiotics, clorobiocin and coumermycin A 1 , L-proline was identified as the precursor for the pyrrole rings, however, the pyrrole rings of undecylprodigiosin are formed in three separate enzymatic processes [51].…”
Section: Biosynthesised Pyrrole Derivativesmentioning
confidence: 99%
“…Its structure consists of a cis-fused octalin ring system linked to a pyrrole-2-carboxylic acid segment. Sushila Maharjan et al investigated the different biosynthetic routes of nargenicin A 1 , providing evidence that the pyrrole moiety present in the compound is also derived from L -proline, owing to the coordinated action of three proteins, NgnN4 (proline adenyltransferase), NgnN5 (proline carrier protein), and NgnN3 (flavine-dependent acyl-coenzyme A dehydrogenases) [51].…”
Section: Biosynthesised Pyrrole Derivativesmentioning
confidence: 99%
“…The diversity of these metabolites is mirrored in the multiple biosynthetic pathways leading to pyrrole groups. Six different biosynthetic pathways have been characterized to date, [1,2] involving various primary metabolite precursors, such as amino acids (glycine, proline, serine, threonine, and tryptophan), [1][2][3][4][5][6][7][8][9][10] dicarboxylic acids (malonate, oxaloacetate, and succinate), [1,2,7,8] or N-(5'-phosphoribosyl)anthranilate. [1] Pyrrolamides are a family of natural products, synthesized by Streptomyces and related actinobacteria, that all contain one or more pyrrole-2-carboxamide moieties in their structure.…”
mentioning
confidence: 99%
“…Cgc11 catalyzes nucleotide triphosphate (NTP)-dependent conversion of 2 into the nucleotide diphosphate (NDP) derivative 3, which undergoes Cgc8-catalyzed oxidation of the C-6 hydroxy group to a carboxy group to yield NDP-2-acetamido-2-deoxyglucopyranuronic acid (4). Cgc9 catalyzes the decarboxylation of 4 to afford NDP-threo-2-acetamido-2-deoxy-pentopyran-4ulose (5). Reductive amination of the C-4 keto group of 5 is catalyzed by the putative pyridoxal-5-phosphate-dependent aminotransferase Cgc12.…”
mentioning
confidence: 99%